2006
DOI: 10.1101/gr.5089806
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution in two large families of ubiquitin-ligase adapters in nematodes and plants

Abstract: Host–pathogen arms races can result in adaptive evolution (positive selection) of host genes that mediate pathogen recognition and defense. To identify such genes in nematodes, I used maximum-likelihood analysis of codon evolution to survey all paralogous gene groups in Caenorhabditis elegans. This survey found robust evidence of positive selection in two classes of genes not previously implicated in pathogen defense. Both classes of genes encode ubiquitin-dependent proteasome adapters, which recruit diverse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(197 citation statements)
references
References 99 publications
(114 reference statements)
9
182
2
Order By: Relevance
“…If so, then we would expect that some F-box proteins have evolved under positive selection. Indeed, in nematodes and plants, it has been suggested that some F-box proteins evolved under positive selection at sites in substratebinding domains (33). However, we showed here that, because of the frequent frame-shift mutations caused by (pseudo)exonization and/or insertions/deletions, the C-terminal sequences may no longer be homologous even between closely related duplicate genes.…”
Section: Discussioncontrasting
confidence: 38%
“…If so, then we would expect that some F-box proteins have evolved under positive selection. Indeed, in nematodes and plants, it has been suggested that some F-box proteins evolved under positive selection at sites in substratebinding domains (33). However, we showed here that, because of the frequent frame-shift mutations caused by (pseudo)exonization and/or insertions/deletions, the C-terminal sequences may no longer be homologous even between closely related duplicate genes.…”
Section: Discussioncontrasting
confidence: 38%
“…[28][29][30] Inhibiting skr-1 or skr-7 by RNAi caused a significant increase in ENU-induced germ cell apoptosis similar to inactivating cul-1 or ned-8 ( Figure 2c and Supplementary Table 1). The increased apoptosis caused by inhibiting cul-1 or skr-1 was abolished in cep-1(gk138) mutants (Figure 2d), suggesting that these genes also act fsn-1 regulates cep-1-dependent signaling in response to DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of SCF ligases is controlled by F-box proteins, which bind to distinct substrate proteins that are targeted for ubiquitin-mediated proteolysis. 26 We systematically inhibited 328 of the 520 predicted F-box genes 28 by RNAi and identified FSN-1, an F-box protein conserved from worm to human that physically associates with RPM-1, SKR-1, and CUL-1 to regulate neuromuscular synapse formation. 31 Using two different null alleles, fsn-1(hp1) and fsn-1(gk429), we confirmed that FSN-1 is a potent negative regulator of ENU-induced germ cell apoptosis ( Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, both rice and Arabidopsis lack the BTB-zinc finger and BTB-BACK-kelch combinations that comprise a substantial percentage of the vertebrate BTB collections (Aravind and Koonin, 1999;Prag and Adams, 2003;Stogios et al, 2005). Rice appears more like C. elegans with respect to the MATH-BTB family Stogios et al, 2005;Thomas, 2006), which is substantially larger relative to Arabidopsis, yeast, and vertebrates (Figure 1).…”
Section: Identification and Characterization Of The Rice Btb Superfamilymentioning
confidence: 99%
“…There is also evidence for large-scale expansions within specific BTB protein subtypes. C. elegans, for instance, has a much larger MATH-BTB family than is present in either insects or vertebrates (Stogios et al, 2005), and there have even been independent expansions of different subsets of the MATH-BTB protein family within individual Caenorhabditis species (Thomas, 2006). One hypothesis to explain this diversity is that each lineage mixed and matched various substrate binding domains with different E3 complex-interacting motifs (e.g., F-box and BTB domains) and then expanded and diversified specific subgroups to handle their own particular sets of Ub targets as each species evolved.…”
Section: Introductionmentioning
confidence: 99%